Causative Factors of Criminal Acts Teacher Mistreatment of Students - Siti Adira Yahya Putri; Suwitno Yutye Imran; Julisa Aprillia Kaluku (Estudiante Law Journal, 2023)
This study investigates the impact of providing restitution on child victims of pornographic video distribution, utilizing empirical legal methods and case-based analysis. The study explores the implementation of restitution for children under Article 7A of Indonesia's Law No. 31/2014 on Witness and Victim Protection and Government Regulation No. 43/2017 on Restitution for Child Victims of Criminal Acts. The research identifies factors influencing the restitution process, including a lack of legal understanding among children, parents, and families of both perpetrators and victims, as well as challenges arising from government regulations on restitution. Restitution, governed by legal frameworks, is recognized as insufficient to eliminate the crime or case resolution. Challenges in restitution fulfillment also stem from the absence of a Witness and Victim Protection Agency, leading to delays in awaiting decisions and assessments from the Central LPSK. Economic capacity and the perpetrator's willingness further impact the restitution process